Early complications, morbidity, and mortality in octogenarians and nonagenarians undergoing posterior intra-operative spinal navigation-based C1/2 fusion for type II odontoid process fractures - Ishak, Basem; Schneider, Till M.; Gimmy, Valerie; Unterberg, Andreas; Kiening, Karl (Journal of neurotrauma, 2017)
Type II odontoid fractures represent the most common cervical spine injury in the elderly. The decision for surgical treatment is still controversial, particularly with regard to the elevated peri-operative risk attributed to frequent comorbidities and poor bone quality. The purpose of this study was to assess both short-term mortality and mid-term clinical and radiological outcome in the elderly. Between January 2007 and December 2015, 35 patients with type II odontoid process fractures who underwent posterior atlanto-axial instrumentation using a modified Goel-Harms technique were retrospectively analyzed and prospectively examined clinically and radiologically. Comorbidities, mortality, and length of intensive care unit (ICU) and hospital stay were determined, as were medical and surgical complications. Quality of life was measured using the EuroQol five dimensions (EQ-5D) and Short Form-36 (SF-36) questionnaires at final follow-up. Average age was 86.5 years. All patients had severe comorbidities pre-operatively. No in-hospital mortality was observed. Average length of hospital stay was 13.8 days and 2.0 days for the ICU. Three patients developed cardiopulmonary complications; one wound infection developed post-operatively. Mean follow-up was 22 months (range, 6-72 months). The quality of life measured by EQ-5D showed a good outcome (0.7 ± 0.1). All SF-36 domains were reduced in comparison to a representative group. Solid bony fusion could be achieved in all patients. Atlanto-axial fusion by using intra-operative spinal navigation is a safe and effective procedure in the elderly, with few complications and preservation of favorable post-operative quality of life. The overall major complication rate was 11%. Surgery in the very old should be considered as first-choice treatment.